High‐resolution electron time‐of‐flight spectrometers for angle‐resolved measurements at the SQS Instrument at the European XFEL. (1st April 2022) - De Fanis, Alberto; Ilchen, Markus; Achner, Alexander; Baumann, Thomas M.; Boll, Rebecca; Buck, Jens; Danilevsky, Cyril; Esenov, Sergey; Erk, Benjamin; Grychtol, Patrik; Hartmann, Gregor; Liu, Jia; et al.
Abstract : A set of electron time‐of‐flight spectrometers for high‐resolution angle‐resolved spectroscopy has been developed for the Small Quantum Systems (SQS) instrument at the SASE3 soft X‐ray branch of the European XFEL. Abstract : A set of electron time‐of‐flight spectrometers for high‐resolution angle‐resolved spectroscopy was developed for the Small Quantum Systems (SQS) instrument at the SASE3 soft X‐ray branch of the European XFEL. The resolving power of this spectrometer design is demonstrated to exceed 10 000 ( E /Δ E ), using the well known Ne 1 s −1 3 p resonant Auger spectrum measured at a photon energy of 867.11 eV at a third‐generation synchrotron radiation source. At the European XFEL, a width of ∼0.5 eV full width at half‐maximum for a kinetic energy of 800 eV was demonstrated. It is expected that this linewidth can be reached over a broad range of kinetic energies. An array of these spectrometers, with different angular orientations, is tailored for the Atomic‐like Quantum Systems endstation for high‐resolution angle‐resolved spectroscopy of gaseous samples.